SISTEM PENGELOLAAN TAMAN BACA MASYARAKAT DI KABUPATEN BARRU - Wisrita wisrita; Andi Rosdianti Razak; Alimuddin Said (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
The purpose of this study was to find out how the community park reading management system in Barru Regency. The type of this research was qualitative descriptive research with informants as many as 5 people. Data collection techniques were collected by using instrument of observation and interviews. The results of this study indicated that the community reading park management system in Barru Regency had been running well, the regional library of Barru Regency coordinated with district, village in terms of further formation of community reading park. Supporting factor was good coordination with the manager. While the inhibiting factors of the community park management system were still lack of books, facilities and infrastructure.